2007
DOI: 10.1590/s0104-42302007000600017
|View full text |Cite
|
Sign up to set email alerts
|

Comparações de medidas de qualidade de vida entre mulheres e homens em hemodiálise

Abstract: INTRODUÇÃOReconhecendo a necessidade de melhorar a qualidade de vida relacionada com a saúde (QVRS) dos pacientes tratados cronicamente por hemodiálise, o Instituto de Medicina dos Estados Unidos e a National Kidney Foundation, por meio do Kidney Disease Outcome Quality Initiative (K/DOQI), recomendam avaliações sistemáticas de escores de QVRS destes pacientes como um dos parâmetros de adequação do tratamento 1 . Além de informar sobre o impacto do tratamento no bem-estar dos pacientes, a avaliação da QVRS aju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
1
4
0
16
Order By: Relevance
“…Despite inconsistencies in the literature regarding the effect of age on QoL of patients on dialysis, the current study showed worsening of the physical component with age, indicating it is a major factor causing limitations in elderly patients. As for gender, QoL tends to be worse among women, 14 a fi nding that was corroborated in the current study. Women on hemodialysis generally have lower QoL than men due to factors other than clinical ones including diffi culty coping with kidney disease, more susceptibility to anemia, anxiety and depressive symptoms with an association between psychological and social factors.…”
Section: Deoreosupporting
confidence: 87%
“…Despite inconsistencies in the literature regarding the effect of age on QoL of patients on dialysis, the current study showed worsening of the physical component with age, indicating it is a major factor causing limitations in elderly patients. As for gender, QoL tends to be worse among women, 14 a fi nding that was corroborated in the current study. Women on hemodialysis generally have lower QoL than men due to factors other than clinical ones including diffi culty coping with kidney disease, more susceptibility to anemia, anxiety and depressive symptoms with an association between psychological and social factors.…”
Section: Deoreosupporting
confidence: 87%
“…Quanto ao gênero, nosso estudo mostrou que as mulheres têm maior prevalência de TMC juntamente com escores menores em sete dos oito domínios do SF-36. Estudos apontam uma similaridade quanto aos nossos achados 44,45 . A qualidade de vida avaliada pelo SF-36 aborda as limitações na vida diária por conte de problemas de saúde, dando uma estimativa subjetiva do estado funcional do indivíduo que, por sua vez, está relacionada à saúde mental.…”
Section: Discussionunclassified
“…Avaliando a categoria sexo e concordando com o estudo de Lopes (38), viu-se que 71,4% das mulheres apresentam níveis mais baixos de QV que os homens, quando comparados aspectos de visão negativa de sua saúde.…”
Section: Discussionunclassified